Sunk Costs and the Variability of Firm Value Over Time - Lambson, Val Eugene; Jensen, Farrell E. (The Review of Economics and Statistics, 1995)
Empirical implications for the variability of firm value in various models of industry evolution are discussed. Under certain conditions, learning models imply that industries with higher sunk costs should exhibit greater difference in firm value between entering and exiting firms whereas external shocks models imply that industries with higher sunk costs should exhibit greater variability of firm value over time relative to a numeraire industry. The theoretical results from external shocks models are consistent with agricultural data from California and Florida. Copyright 1995 by MIT Press.